- Crusader Philippe Conte Flanders (Alsace) through the book of the history of the overseas business Lolim Suri)1179- 1177/(573- 575 - Analytical and Critical Study - Al Harbi, Aisha Bint Murshoud Hamid (Journal of Humanities & Social Sciences, 2018)
The purpose of this research is to present the crusade of Philippe Conte Flanders and its impact on the Crusader movement، especially as it was hoped by the Crusader princes in the Orient. We will also be exposed to Saladin's efforts to repel any attempt by Philippe to support the Crusader presence. To achieve any decisive victory for the crusaders.
Keywords: Baldwin IV; Tall al-Jazr; Battle of Ramla; Raymond III; Manuel Comnene; Harem